Tax Stabilisation, Trade and Political Transitions in Francophone West Africa over 120 Years - Jens Andersson (African Economic History Network (AEHN), 2018)
Contemporary African fiscal systems are usually portrayed as being subject to significant instability, which has negative consequences for public spending and development. However, this paper documents significant long-term fiscal stabilisation in Benin, C\~AƒÂte d'Ivoire, Niger and Senegal as measured by reductions in tax revenue instability and the responsiveness of tax revenue to trade over a 120-year period. This historical process of long-term fiscal stabilisation in francophone West Africa has not been properly acknowledged in the contemporary fiscal policy literature that tends to focus on recent decades. Moreover, it is shown qualitatively and econometrically that this fiscal stabilisation has been accompanied with a longterm reduction in the volatility of trade, a change in tax composition away from trade taxes to indirect domestic taxes, and major shifts in development policy paradigms. This points to the value of studying African fiscal systems over long periods of time to identify relationships not apparent from a short-term perspective and understand the intricate mechanisms and dynamics that characterize the development process.
Keywords: N01; N17; N27; N47; 330; Financial capacity; tax stabilisation; French West Africa; economic hitsory